Knowledge Levels and Attitudes Toward Cybercrimes of Adolescents in Northern Cyprus - Özdamlı, Fezile; Ercag, Erinc (TEM Journal, 2019)
Besides the many positive effects of the use of information technologies, it also generates many problems. It is especially of great importance to determine the level of knowledge and awareness of individuals on the cybercrime. No studies have been conducted on this issue in the Turkish Republic of Northern Cyprus. Based on this, it was necessary to determine the knowledge level of adolescents who are frequent users of digital technologies regarding the cybercrimes and their attitudes toward them. This study is a descriptive survey model. The working group is composed of 407 adolescents in the TRNC. The data collection tool was “Concepts of Informatics and Student Opinion Survey on Cyber Crimes” developed by Gozler and Tasci (2015). The 5 point Likert scale questionnaire consists of 16 items. Frequency, percentage and mean analysis was applied during the data analysis. It is clear that cybercrime awareness in Northern Cyprus has to be increased.